POLITIK DALAM PERJANJIAN LAMA DAN HUBUNGANNYA TERHADAP GEREJA - Junaedi Junaedi; Septian Dannari, Martinus Kindak (ADISAM PUBLISHER, 2024)
This article is entitled Study of Politics ìn the Old Testament and its Relationship to the Church. This article aims to understand the political situation in the Old Testament and try to relate it to the church in relation to the current way of church politics. This paper uses qualitative research methods. From this research, it was found that basically humans are a political zoon, therefore human life will aways be related to politics. Politics is always closely related to power, so this power is an important issue as to why God must continue to be present in every process of human life, especially for those as leaders both in the congregation and society in general.